Male sterile maize inbred lines - CGIAR Research Program on Maize (2019)
Male sterile versions of four elite CIMMYT-Asia inbred lines have been developed, displayed and are ready for distribution. These are good source breeding material for partners wanting to develop male sterility systems. Partners with licensed hybrids involving these lines may consider using these for product development.